Analysis of the implementation of defense economic policy in strengthening cyber capacity in Indonesia - Al Khoiriyah, Nurul Faizah; Suwito, Suwito; Iswati, Sri (Journal of Economics and Business Letters, 2025)
Strengthening cyber capacity has become an important component of Indonesia's defense economic framework, along with the development of technology and increasing cyber threats that can affect economic stability and national security. This study aims to analyze the implementation of defense economic policies to strengthen Indonesia’s cyber capacity. The research method used a qualitative approach with a literature study through policy document analysis and budget data, applying George C. Edward III's policy implementation framework which focuses on four key variables: communication, resources, disposition, and bureaucratic structure. The results show that the integration of Indonesia’s defense, economic, and cyber policies has not been fully optimized. The findings indicate that without structural adjustments, the policy will remain normative. Therefore, an adaptive defense economic transformation is needed, placing cyber security as a strategic component by strengthening communication between institutions, increasing investment in human resources and technology, and synergy between defense institutions through bureaucratic simplification.